1997
DOI: 10.1046/j.1365-2141.1997.1562968.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute basophilic leukaemia and translocation t(X;6)(p11;q23)

Abstract: Summary.We report two infants with acute basophilic leukaemia associated with a t(X;6)(p11;q23) as the sole abnormality. Morphologic evidence of basophilic lineage was provided by light and electron microscopy. Both patients also had a similar presentation on diagnosis, characterized by clinical signs consistent with a hyperhistaminaemia syndrome, i.e. urticarian rashes and gastro-intestinal disorders evocative of peptic ulcer. Immunophenotypes differed in the two patients, one expressing CD24, CD13 and CD33, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…4 The t(X;6)(p11;q23) rearrangement has been already described in few previous cases, although the corresponding bps have not been cloned. In particular, Dastugue et al described two infant patients, 8 affected by acute basophilic leukemia (see Supplementary Table 2 for the comparison of the two patients with our case). We do not have enough elements to assess the presence of a similar leukemia in our patient, who showed a very aggressive phenotype, as confirmed by the lack of a response to treatment.…”
Section: As Indicated Inmentioning
confidence: 99%
“…4 The t(X;6)(p11;q23) rearrangement has been already described in few previous cases, although the corresponding bps have not been cloned. In particular, Dastugue et al described two infant patients, 8 affected by acute basophilic leukemia (see Supplementary Table 2 for the comparison of the two patients with our case). We do not have enough elements to assess the presence of a similar leukemia in our patient, who showed a very aggressive phenotype, as confirmed by the lack of a response to treatment.…”
Section: As Indicated Inmentioning
confidence: 99%
“…Conventional cytogenetic examination using GTG banding revealed a complex karyotype, with multiple numerical and structural aberrations (14 metaphases with structural anomalies consisting of t(1;4) (p35;q35), del(5)(q31->qter), t(5;20)(p15;p13) and 17 metaphases with numeric anomalies: 11 metaphases with hyperdiploidy (47-50 chromosomes) and 6 metaphases with hypodiploidy. t (9,22) or t(6,9) were not identified. del(5)(q31->qter) was confirmed by interphase fluorescence in situ hybridization (FISH) testing ( Figure 3).…”
Section: Case Reportmentioning
confidence: 99%
“…Differential diagnosis includes other myeloid neoplasms associated with basophilia, namely AML with t(6;9)(p23;q14), acute promyelocytic leukemia with basophilic differentiation, blastic transformation of chronic myelogenous leukemia, primary myelofibrosis, or rare acute lymphoblastic leukemia cases with prominent cytoplasmic granules [1,4]. Noteworthy, even though multiple chromosomal abnormalities have been reported involving chromosomes 1, 2,6,7,8,11,12,16,17,19,21 and X, no recurrent cytogenetic or molecular anomalies have been described in acute basophilic leukemia patients [3,[5][6][7][8][9][10][11][12][13]. Acute basophilic leukemia management remains poorly defined, relying on cytarabine and anthracycline-based induction regimens, palliative cytoreductive treatment, targeted therapies (tyrosine kinase inhibitors) or allogeneic stem cell transplant in selected cases [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…Patients P1 and P2 have been reported previously. 4 Because of its location on chromosome 6q23 and its well established involvement in oncogenesis, 7 MYB was a good candidate gene. Our molecular investigations, based on fluorescence in situ hybridization (FISH) and rapid amplification of cDNA ends (RACE), revealed that the translocation generated a MYB-GATA1 fusion gene.…”
Section: Introductionmentioning
confidence: 99%
“…Rare cases of t(X;6)(p11;q23) translocations have been reported but these were sporadic. [4][5] Of note, a very recent paper reported the cloning of the t(X;6)(p11;q23) in a case of acute monoblastic leukemia. 6 We report here 4 cases of ABL with a t(X;6)(p11;q23) translocation occurring in male infants.…”
mentioning
confidence: 99%